Nereididae (Annelida: Phyllodocida) from intertidal macroalgae in Western Australia - Hadiyanto, Hadiyanto; Glasby, Christopher J (Zootaxa, 2023)
The last extensive exploration of Nereididae diversity within coastal waters of Western Australia was done in 1975–1984. We collected Nereididae associated with macroalgae from 38 rocky intertidal shores of Western Australia (18°S to 34°S). Eighteen species belonging to seven genera are described and illustrated. Two new species, Nereis edentata n. sp. and Nereis yuedensis n. sp., were found. Nereis edentata n. sp. differs from other Nereis species having one row of paragnaths on Areas VII–VIII and smooth notopodial homogomph falcigers in posterior chaetigers. Nereis yuedensis n. sp. differs from other Nereis species having one row of paragnaths on Areas VII–VIII and notopodial homogomph falcigers with at least one large lateral tooth, and also species having notopodial homogomph falcigers starting from chaetiger 3. The distribution of N. yuedensis n. sp. was found to be restricted within temperate Australia and N. edentata n. sp. appears to be transitional between temperate and tropical regions. Also, we remove from synonymy the probable Western Australian endemic species, Pseudonereis rottnestiana (Augener, 1913), and provide a key to all known genera and species of Nereididae from Western Australian waters.